Optimisation of regeneration conditions of Norway spruce microplants from highly productive embryogenic line - Kusenkova, Marina P. (Experimental Biology and Biotechnology, 2023)
The article presents the results of the study on the influence of nutrient media-composition, including the abscisic acid in different concentrations, on somatic embryo maturation and germination. The callus tissue of Norway spruce highly productive cell line (M2), obtained from seeds of Belarusian origin, was selected as the object of experimental study. Among the tested variants of abscisic acid concentration (15; 30 and 60 mmol/L) during somatic embryo maturation stage using the last two gave a pronounced positive effect. It has been showed that Litvay medium with the halfstrength macrosalts and the addition of activated charcoal (5 g/L) and glutamine (0.5 g/L) is optimal for the somatic embryo germination stage.